Sales Process as a Service (SPAS): Development and Validation of an Extension to the Shortened Selling Orientation – Customer Orientation (SOCO) Score (SOCO-SPAS) - Ledinger, Stefan (Naše gospodarstvo/Our economy, 2022)
The association between selling orientation and customer orientation and sales success has been a matter of intensive research since the publication of the selling orientation-customer orientation (SOCO) score in the early 1980’s. However, which attitudes predispose salespeople for high perfor-mance remains elusive. In addition, the association between customer orientation may be curvilinear and depend on the selling situation– and little research has been devoted to business-to-business (B2B) sales. This paper aims at starting to close those knowledge gaps through the development of a self-assessment tool for attitudes of salespeople. An extension of the 10-item SOCO score is developed through literature research in sales/business development and on service orientation in other settings. The score was subsequently validated through feedback by sales scholars. The extended score adds a dimension that tests whether professional salespeople consider the sales process as a service (SPAS) that should provide value beyond the identification of the best offering. Response rates by sales scholars was low, resulting in the need for further validation of the candidate SOCO-SPAS score. Business-to-business (B2B) relationships are an essential but understudied area of economics. The current paper provides a means to assess the relationship between attitudes and sales performance in modern B2B sales, by extending a scoring system that has originally been developed for B2C sales and many years in the past when market conditions were different than today.
Keywords: Sales process; B2B sales; Customer orientation; Service orientation; Self-assessment